Bionomics of Freyeria trochylus (Freyer, 1844) and Zizeeria karsandra (Moore, 1865) (Lepidoptera, Lycaenidae) on Rodos Island, Greece - Christos J. Galanos (Nota Lepidopterologica, 2020)
This study is focused on the presence of Freyeria trochylus (Freyer, 1844) and Zizeeria karsandra (Moore, 1865) on Rodos Island, Greece. F. trochylus was first found there by Turati and Fiori in 1923 and Z. karsandra by Bender in 1958. The distributional range of both species in Europe including the Mediterranean and their habitat and ecology, including their associations with ants, together with their life history and larval hostplants are examined. The life cycle of Z. karsandra is described and illustrated here for the first time for Europe as a whole.